Ecosystem services and associated concepts - Dick, J. McP; Smith, Rognvald I.; Scott, E. Marian (Environmetrics (London, Ont.), 2011)
In this paper, we explore the practicality and limitations of the ecosystem services concept. The enthusiasm for the analytical investigation of services delivered by ecosystems is driven by the realisation that local, national and international policies are not protecting ecosystems and the full range of services they deliver to humans. We briefly review the history of the term and consider a range of analytical frameworks proposed to study ecosystem services. The problem of understanding ecosystems across varying spatial and temporal scales is a recurring theme and we argue that systems analysis such as world‐systems and panarchy analysis is useful in this context. Translating any one of these frameworks to an operational definition presents some challenges, which are briefly discussed in terms of measurement and quantification. Copyright © 2011 John Wiley & Sons, Ltd.